2017
DOI: 10.1002/2016jc012059
|View full text |Cite
|
Sign up to set email alerts
|

Wind modulation of upwelling at the shelf‐break front off Patagonia: Observational evidence

Abstract: The South‐Atlantic Patagonian shelf is the largest chlorophyll‐a (Chl‐a) hot spot in Southern Ocean color images. While a persistent 1500 km long band of high Chl‐a along the shelf‐break front (SBF) is indicative of upwelling, the mechanisms that drive it are not entirely known. Along‐front wind oscillations can enhance upwelling and provide a nutrient pumping mechanism at shelf‐break fronts of western boundary currents. Here we assess wind‐induced upwelling at the SBF off Patagonia from daily satellite Chl‐a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 97 publications
(220 reference statements)
5
34
2
Order By: Relevance
“…Finally, remote and in situ observations of fronts can be used to assess the relationships between unsteady winds and biogeochemistry and to test whether the observations are consistent with existing models (see Carranza et al . [] for a recent observational study that focuses on the role of synoptic along‐front wind variability in modifying surface chlorophyll at a front, similar to this study). In any case, the analysis presented here builds on and supports existing studies that suggest wind‐driven vertical transport at fronts, via both turbulent mixing and vertical advection, has a significant impact on biology at fronts in real nutrient‐limited open oceans.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Finally, remote and in situ observations of fronts can be used to assess the relationships between unsteady winds and biogeochemistry and to test whether the observations are consistent with existing models (see Carranza et al . [] for a recent observational study that focuses on the role of synoptic along‐front wind variability in modifying surface chlorophyll at a front, similar to this study). In any case, the analysis presented here builds on and supports existing studies that suggest wind‐driven vertical transport at fronts, via both turbulent mixing and vertical advection, has a significant impact on biology at fronts in real nutrient‐limited open oceans.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…A budget analysis for 〈Fe〉 along the ACC (Figures b and d; see the supporting information for details) quantifies the various mechanisms of iron supply and removal. We only consider areas where bathymetry is deeper than 200 m in order to avoid the direct influence from shelf regions (Carranza et al, ). Iron is supplied to the mixed layer by lateral and vertical advection, vertical mixing, aeolian input of dust, and entrainment associated with changes in the MLD; it is removed through the biogeochemical sink term, which represents phytoplankton uptake and scavenging on sinking particulates.…”
Section: Mechanisms In An Eddy‐rich Biogeochemical Modelmentioning
confidence: 99%
“…The Patagonian Shelf Large Marine Ecosystem (PLME) (Heileman, 2009) is one of the widest in the world, one of the most productive (Lutz et al, 2010), and hydrographically complex in the Southern Hemisphere (Palma et al, 2008;Matano et al, 2010;Paniagua et al, 2018). The extensive shelf breakfront and other shelf fronts support high phytoplankton productivity and fisheries incomes (Acha et al, 2004;Carreto et al, 2016;Carranza et al, 2017;Díaz et al, 2018). Moreover, recent studies on satellite images showed that chlorophyll a (chl-a) has notably risen over the last two decades (Marrari et al, 2017), which highlights the role of this large ecosystem in the global carbon uptake and in the regional sustainability of marine resources and stakeholder communities (Bianchi et al, 2009;Marrari et al, 2013).…”
Section: Introductionmentioning
confidence: 99%